Global COVID-19 Pandemic: Prevention and Protection Techniques - Mohajan, Haradhan Kumar (Journal of Economic Development, Environment and People, 2021)
The COVID-19 is an infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). It has been identified as the causative agent of the viral pneumonia outbreak in Wuhan, China, at the end of 2019. It has a high human to human transmission capability and primarily targets the human respiratory system. Healthcare providers to common people are in high risks of the contamination of this fatal disease. It spreads person to person through respiratory droplets that produced during talking, coughing and sneezing. It is associated with severe and fatal respiratory disease in humans. At present it becomes great global public health concern. On 11 March 2020, the WHO declared the global COVID-19 outbreak as a pandemic. The COVID-19 pandemic has entered in a very dangerous phase in April and May 2020, and the severity is increasing day by day. On 26 July 2020, about 216 countries and territories are infected worldwide; total global infections become more than 16.3 million and total recovered about 9.9 million with total deaths 648,477. The disease have not abolished even in the 2021. On 09 February 2021, the disease spread up to 223 countries and territories globally; total confirmed deaths become 2,337,368, total confirmed cases 107,037,441, with total recovery 78,913,746. The paper discusses the social, economic, and health impacts in the world’s poorest countries due to COVID-19 pandemic outbreak. The study also presents the current economic situation of the world and analyses the potential consequences on global economy. An attempt has been taken here to create consciousness among the common people to reduce the fatality of this killer disease. From the beginning of 2021, COVID-19 vaccines are distributed worldwide and all nations are united to abolish the virus completely.